A self-healing layered GeP anode for high-performance Li-ion batteries enabled by low formation energy. (July 2019) - Li, Wenwu; Li, Xinwei; Yu, Jiale; Liao, Jun; Zhao, Bote; Huang, Liang; Ali Abdelhafiz,; Zhang, Haiyan; Wang, Jeng‐Han; Guo, Zaiping; Liu, Meilin
Abstract: Ge is considered a promising anode candidate for Li-ion batteries (LIBs); however, its practical applicability is hindered by the relatively slow Li-ion diffusion owing to the stiffness of the diamond-like structure. Inspired by little difference in electronegativity between Ge and P, we have designed a novel layered GeP anode for LIBs, which can be readily synthesized using a mechano-chemical method and a subsequent low-temperature annealing. In particular, GeP demonstrates the best performances among all Ge-based anode materials studied, attributed to its fast Li-ion diffusion compared to Ge counterpart and a unique Li-storage mechanism that involves intercalation, conversion, and alloying, as confirmed by XRD, TEM, XPS, and Raman spectroscopy. Specially, the initial layered crystal structure of GeP can be reconstructed during charging due to its low formation energy, thus offering remarkable reversibility during cycling. Further, this study implies that the formation energy of crystal structures could be an important parameter for strategic design of large-capacity anode materials for LIBs. Graphical abstract: A novel layered Ge-based GeP is originally prepared by a scalable mechanochemical method with a subsequent low-temperature annealing and initiated as anode for Li-ion batteries. The as-synthesized GeP delivers a self-healing Li-storage mechanism profiting from its low formation energy as unraveled by first-principle calculation, thus enabling its carbon composite with the best performances among the Ge-based anodes studied. Image 1 Highlights: Layered GeP is prepared by a scalable mechanochemical method and a annealing process. The anode shows large capacity, high initial coulombic efficiency and long-cycling life. The anode has higher Li-ion conductivity than that of Ge and experimental validation. The high reversibility is attributed to the low formation energy as unraveled by DFT calculation. The formation energy could be a parameter for rational design of anode materials for LIBs.